Gallbladder wall thickening in a woman with postpartum preeclampsia: A case report - Tsuyoshi Murata; Yuki Yoshimoto; Yoshiaki Shibano; Soichi Nakamura; Ryuji Yamauchi (Elsevier, 2022)
Background: Preeclampsia (PE) is hallmarked by dysfunction of various organs; therefore, its diagnosis can be challenging, especially when patients present with right upper abdominal pain. Herein, we present a case of postpartum gallbladder wall thickening (GBWT) that led to a diagnosis of PE, rather than hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome or gallbladder and biliary disease. Case Presentation: A 31-year-old postpartum woman presented with a fever, hypertension, headache, and right upper abdominal pain. HELLP syndrome and intracranial hemorrhage were initially suspected, due to the combination of symptoms and elevated levels of aspartate transaminase, alanine transaminase, and lactate dehydrogenase. However, hemolysis and thrombocytopenia were absent, and a computed tomography (CT) scan of the head did not indicate the presence of intracranial hemorrhage. Further, transabdominal ultrasound and CT revealed GBWT (edematous gallbladder); CT also revealed an enlarged heart, lung edema, pleural effusion, and ascites. Thus, PE, rather than HELLP syndrome or gallbladder or biliary disease, was diagnosed based on gestational hypertension and proteinuria, new-onset headache, liver dysfunction, and edema in several organs, including the lung. Nicardipine treatment quickly improved hypertension and headache, and, over time, the patient's urination increased, and edema subsided throughout the body. Furthermore, laboratory results improved, and the patient was discharged on postpartum day 11. Conclusion: Postpartum gallbladder wall thickening can be a diagnostic sign of PE.